Infographic. Successful hosting of a mass sporting event during the COVID-19 pandemic - Hagemann, G.; Hu, C.; Al Hassani, N.; Kahil, N. (British Journal of Sports Medicine, 2021)
In a previous BJSM blog posted in April this year Nitin K Sethi posed the question, `Amid the COVID-19 pandemic should combat sports events be held `behind closed doors`? The article`s conclusion was that with the right preparation and `by adopting some of the above practices a cautious start to combat sports events can be contemplated`. Within this context, the Ultimate Fighting Championship (UFC) elected to hold a series of fights on Yas Island, Abu Dhabi, hosted by the Department of Culture and Tourism and in close liaison with the Department of Health, from 01 to 31 July 2020.